Precipitation and temperature drive microbial community changes affecting flavor quality of Nongxiangxing Daqu - Tongwei Guan; Xinyue Wei; Xianping Qiu; Ying Liu; Jianshen Yu; Rui Hou; Maoke Liu; Yichen Mao; Qingru Liu; Lei Tian; Zongjun He; Shuangquan Xiang (Food Chemistry: X)
Nongxiangxing Baijiu is the most famous Baijiu flavor in China, and its characteristic style is closely related to Nongxiangxing Daqu used in fermentation. However, there are few reports about the difference of Daqu quality between seasonal variations. In this study, precipitation and temperature drove changes in microbial communities that resulted in differences in the flavor of Daqu produced in different seasons. For example, the average daily temperature in summer was as high as 27.29 ± 2.24 °C, which was significantly higher than other seasons (p < 0.01). Bacillus was abundant in the Daqu produced in this season, while tetramethylpyrazine flavor was more prominent, up to 1556.95 ± 153.92 μg/kg. Metabolomics studies identified major pathways associated with the weak flavor of spring_Daqu. In addition, LEFSe analysis revealed the marked microorganisms in different seasons. These results revealed the differences in seasonal Daqu, thus contributing to the scientific and rational use of Daqu.